The challenge of social services development – the establishment of welfare pluralism in social services - Žalimienė, Laimutė (Socialinė teorija, empirija, politika ir praktika, 2006)
The goal of the paper is to present the development of welfare pluralism in the area of social services in EU and Lithuania. The characteristics, benefits and limitations of actors are analysed in the paper. The literature analysis was done in order to obtain conclusions. The results of analysis suggest the existence of different modes of social service provision in different European Countries. The different actors are dominating in the welfare market. The requirement for welfare pluralism is the equality of conditions and opportunities to participate in social service provision. The transition to welfare pluralism requires the establishment of social service funding and purchasing system.
Keywords: Social services; Welfare pluralism; Service providers